Crosstalk between miR‐215 and epithelial‐mesenchymal transition specific markers (E‐cadherin and N‐cadherin) in different stages of chronic HCV Infection. Issue 8 (30th December 2019) - Omran, Nermeen M.; El‐Sherbini, Sherif M.; Hegazy, Osama; Elshaarawy, Ahmed A.; Talaat, Roba M.
Abstract: The main causes of death among patients with hepatocellular carcinoma (HCC) are a recurrence, metastasis, and deterioration of primary tumors by the epithelial‐to‐mesenchymal transition (EMT) which is controlled by several molecules including E‐cadherin and N‐cadherin. Microribonucleic acids (miRNAs) have been identified to play a regulatory role in EMT. miR‐215 is important in repressing migration/invasion of cancer cells. In this study, we aimed to evaluate the crosstalk between miR‐215 and EMT specific markers (E‐cadherin and N‐cadherin) with a spotlight on its role in the EMT process in hepatitis C virus (HCV)‐infected patients. One hundred forty‐five patients were studied, 75 had HCV‐induced cirrhosis classified into child A, B, and C and 25 had HCC. In parallel, 45 healthy volunteers considered as controls. Serum levels of E‐ and N‐cadherin were measured using enzyme‐linked immunosorbent assay and miR‐215 expression measured by a quantitative reverse transcription‐polymerase chain reaction. Insignificant change in serum levels of E‐cadherin and N‐cadherin in HCV‐infected patients compared with normal controls was observed with a slight increase in E‐cadherin and N‐cadherin in the child B group. HCC patients had the lowest amount of E‐cadherin and N‐cadherin compared with cirrhotic and normal subjects. A maximum reduction in miR‐215 was observed in HCC patients compared with cirrhotic and control ones. A positive correlation ( r = .202; P < .05) was observed between miR‐215 and E‐cadherin. Our data stressed on the potential role of miR‐215 as an important mediator in HCC progression. miRNAs participating in EMT needs further studies to provide insight into the metastasis of HCC. Highlights: Relation between miR‐215 and EMT specific markers were studied in HCV infected patients. Insignificant change in serum levels of E‐ and N‐cadherins in HCV infected patients. Maximum reduction in miR‐215, E‐ and N‐cadherins was observed in HCC group of patients. A positive correlation was observed between miR‐215 and E‐cadherin. miR‐215 might be considered as one of the important mediators in HCC progression.